Differential and interactive effects of temperature and photoperiod on budburst and carbon reserves in two co-occurring Mediterranean oaks - Sanz-Pérez, V.; Castro-Díez, P.; Valladares, F. (Plant Biology, 2009)
Effects of temperature and photoperiod and their interactions on budburst and on the use of carbon reserves were examined in two Mediterranean oaks differing in wood anatomy and leaf habit. Seedlings of Quercus ilex subsp. ballota (evergreen and diffuse-porous wood) and Q. faginea (semi-deciduous and ring-porous wood) were grown under two temperatures (12 and 19 °C) and two photoperiods (10 and 16 h) in a factorial experiment. In the 16 h photoperiod at 19 °C, photosynthesis was suppressed in half of the seedlings by covering leaves with aluminium foil. The concentration of soluble sugars, starch and lipids in leaves, stems and roots was assessed before and after budburst. Under the 12 °C treatment (mean current temperature in early spring in the Iberian Peninsula), budburst in Q. faginea occurred earlier than in Q. ilex. Higher temperature promoted earlier budburst in both species, mostly under the 16 h photoperiod. This response was less pronounced in Q. faginea because its budburst was also controlled by photoperiod, and because this species needs to construct a new ring of xylem before budburst to supply its growth demands. Therefore, dates of budburst of the two species became closer to each other in the warmer treatment, which might alter competitive relations between the species with changing climate. While Q. ilex relied on carbon reserves for budburst, Q. faginea relied on both carbon reserves and current photoassimilates. The different responses of the two Quercus species to temperature and photoperiod related more to xylem structure than to the source of carbon used for budburst.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Global warming; Lipids; Phenology; Quercus faginea; Quercus ilex; soluble sugars; starch; wood anatomy